Bibliometric Analysis of Ocean Literacy Trends in Science Education Research (2003-2023) - Dewi, Tisrin Maulina; Indriyanti, Dyah Rini; Madnasri, Sutikno; Sanusi, Rahmat (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
Studies on ocean literacy in science education have gained increasing attention from scholars in recent years. To provide an overall understanding of these scientific contributions, a bibliometric analysis was conducted on 117 journal articles collected from the Scopus database. The analysis was carried out using Biblioshiny and VosViewer tools to investigate trends and patterns in the field of ocean literacy within science education. The results revealed that publications on ocean literacy in science education have increased exponentially, with an annual growth rate of 0.86%. Key terms related to ocean literacy in science education include education, literacy, oceanography, climate change, teaching, learning, ocean literacy, and students. Emerging study topics include sustainable development, citizen science, marine environment, communication, and environmental education. The findings provide an overview for science educators to develop research studies on ocean literacy and present a valuable framework for continuous research in this area. This study highlights aspects of ocean literacy that have not been extensively explored and can serve as a valuable resource for researchers, educators, and stakeholders engaged in the sustainable conservation of the ocean in the future.